2016
DOI: 10.1021/acs.jpcc.6b03106
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Theoretical Study of Ethylene Adsorption on δ-MoC(001), TiC(001), and ZrC(001) Surfaces

Abstract: A systematic study of ethylene adsorption over δ-MoC(001), TiC(001), and ZrC(001) surfaces was conducted by means of calculations based on periodic density functional theory. The structure and electronic properties of each carbide pristine surface had a strong influence in the bonding of ethylene. It was found that the metal and carbon sites of the carbide could participate in the adsorption process. As a consequence of this, very different bonding mechanisms were seen on δ-MoC(001) and TiC(001). The bonding o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
36
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(39 citation statements)
references
References 58 publications
3
36
0
Order By: Relevance
“…Similar conclusions were obtained for methane adsorption on the same surfaces[47]. Not unexpectedly, the adsorbate molecular geometry remains unchanged[16,47].…”
supporting
confidence: 81%
See 1 more Smart Citation
“…Similar conclusions were obtained for methane adsorption on the same surfaces[47]. Not unexpectedly, the adsorbate molecular geometry remains unchanged[16,47].…”
supporting
confidence: 81%
“…Owing to their activity and the fact that they do not require special conditions for their synthesis [15], Mo carbides have stood out among other TMCs. Very recently it has been shown that the interaction of ethylene with -MoC(001) and Pt(111) exhibits a similar adsorption energy [16], further reinforcing the idea that early TMCs exhibit chemical features of late transition metals. On the other hand, Mo2C phases have been proposed as alternative to commercial catalyst for water gas shift reaction (WGS) [17] and Pt/Mo2C based catalyst also display very high rates for WGS [18].…”
Section: Introductionmentioning
confidence: 69%
“…5,21,22 Among the crystal phases of molybdenum carbide, 23 three of them are the most used in catalysis, viz. cubic, 13,22,[24][25][26][27][28][29] hexagonal 11,[30][31][32] and orthorhombic. 14,20,22,28,33 In general, molybdenum carbides can be represented as MoC y , where the most investigated system is y = 0.5 (Mo 2 C), i.e.…”
Section: Introductionmentioning
confidence: 99%
“…However, phases with y = 1 (MoC) have also been reported. 22,25,28,29,34,35 Moreover, y also could be a non-integer number, leading to nonstoichiometric carbides. 13 The chemistry of molybdenum carbides depends on their C/Mo ratio, with a significant effect in the activity, stability, and selectivity in hydrogenation reactions.…”
Section: Introductionmentioning
confidence: 99%
“…[117] Crystal phase plays a significant role in the intrinsic characteristics of molybdenum carbide including the type of supersaturation, catalyst geometry, and interfacial energy. [117,[148][149][150] A series of phases in molybdenum carbides (Mo x C), such as α-Mo 2 C, β-Mo 2 C, γ-MoC, η-MoC, δ-MoC, and α-MoC 1−x , show quite different electrochemical performances due to the varied electronic configurations. [116] Rodriguez and co-workers revealed the different d-band center values on δ-MoC (−4.79 eV), α-MoC (−3.18 eV), and β-Mo 2 C (−3.02 eV) by the DFT calculations, [42] which were related to the binding strength of H-binding on the surface and consequently lead to the different HER activity.…”
Section: Crystal Structure and Support Effectsmentioning
confidence: 99%